The Correctional System Revitalization: the Understanding Required to Revitalize Convicts'Correctional Facilities - Sulistyanta, Sulistyanta; Shaifu, Awwal Muhammad (Yustisia, 2021)
This research describes the individualization of convict coaching and the special penitentiary for certain convicts. It also analyzes the understanding required to revitalize convicts' correctional facilities, which assess changes in treatment regarding those with "good behavior." Furthermore, this research examined the possibility of revitalizing convicts' penitentiary to focus on the security approach. When the basic concept of the revitalization of the penitentiary is focused on the level of "treatment," which is based on the assessment criteria of "good behavior of the convicts," the convicts are placed in the penitentiary with minimum security. Furthermore, this change assesses the ability to change the existing treatment system for convicts. This is normative legal research, with data obtained from primary and secondary legal materials through literature study. The results showed that the individualization of coaching rests on the fact of the convicts' heterogeneity based on their classification, which affects the type of coaching applied. This variety of coaching affects the facilities and infrastructure needed therefore it is based on the heterogeneity of convicts the need special Penitentiary.